2018
DOI: 10.1136/bmj.k207
|View full text |Cite
|
Sign up to set email alerts
|

Five and 10 minute Apgar scores and risks of cerebral palsy and epilepsy: population based cohort study in Sweden

Abstract: ObjectiveTo investigate associations between Apgar score at five and 10 minutes across the entire range of score values (from 0 to 10) and risks of childhood cerebral palsy or epilepsy, and to analyse the effect of changes in Apgar scores from five to 10 minutes after birth in infants born ≥37 completed weeks.Design, setting, and participantsPopulation based cohort study in Sweden, including 1 213 470 non-malformed live singleton infants, born at term between 1999 and 2012. Data on maternal and pregnancy chara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
78
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(93 citation statements)
references
References 39 publications
11
78
0
1
Order By: Relevance
“…A low Apgar score at 5 minutes after delivery has been associated with a longterm health impairment. 21,23,24 In the present study, after adjustment a reduced risk of NICU transfer was observed in TOLAC compared with non-TOLAC. Most previous research appears to support the view that the risk of NICU transfer in TOLAC deliveries is not higher than in non-TOLAC.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…A low Apgar score at 5 minutes after delivery has been associated with a longterm health impairment. 21,23,24 In the present study, after adjustment a reduced risk of NICU transfer was observed in TOLAC compared with non-TOLAC. Most previous research appears to support the view that the risk of NICU transfer in TOLAC deliveries is not higher than in non-TOLAC.…”
Section: Discussionsupporting
confidence: 53%
“…21 A Swedish population-based study reported a 5-minute Apgar score < 7 in 1.8% of TOLAC deliveries vs 1.1% in non-TOLAC. 21,23,24 In the present study, after adjustment a reduced risk of NICU The induction rate in TOLAC in the present study was 21% (all methods). 12 Obtained in deliveries comprising maternal choice, this agrees with our findings in low-risk pregnancies.…”
Section: Discussionsupporting
confidence: 49%
“…Apgar score and the need for neonatal resuscitation was correlated to subsequent risk of CP . In our cohort, 22.7% of dyskinetic CP infants had an Apgar score below five at five minutes as compared to <0.5% in the general population . This is a considerable difference and higher than what is seen in bilateral spastic CP infants (11.2%).…”
Section: Discussionmentioning
confidence: 53%
“…However, whether consequences of early life exposure to stress, signalled by a low Apgar score, are associated with low stress resilience persisting until adolescence has been incompletely described. Previous studies have shown an increased risk of chronic disease in children with low Apgar scores (13)(14)(15). A low Apgar score at five minutes is likely to confer a higher risk than a correspondingly low score at one minute, as a prolonged low score is likely to signal more than just transient distress associated with delivery.…”
Section: Key Notesmentioning
confidence: 97%